Focal therapy in prostate cancer and advances in the use of androgen blockade - Hernandez, Carlos; Martinez-Salamanca, Juan Ignacio; Maiolino, Giuseppe; Miñana, Bernardino; Gómez-Veiga, Francisco (Frontiers in Urology, 2025)
Focal therapy (FT) for localized prostate cancer (PCa) has evolved into a precision-based alternative to radical treatments, aiming to eradicate clinically significant disease while minimizing functional morbidity. This review provides an updated and critical synthesis of the current landscape of FT, emphasizing the central role of multiparametric magnetic resonance imaging (mpMRI) and fusion biopsy in patient selection, treatment planning, and post-therapy evaluation. mpMRI enables accurate lesion characterization, identification of index lesions, and tailored ablation with energy sources such as high-intensity focused ultrasound (HIFU), cryotherapy, irreversible electroporation (IRE), vascular-targeted photodynamic therapy (VTP), and interstitial laser therapy (ILT). Across modalities, continence preservation exceeds 90%, and erectile function is maintained in up to 100% of patients, underscoring the functional safety of FT. While current evidence supports FT as an oncologically sound option for low- and select intermediate-risk disease, data from phase III trials remain scarce. Emerging strategies integrating androgen deprivation therapy (ADT) with FT show promise in enhancing tumor control, particularly in high-risk, large-volume, or anatomically complex cases. Preliminary studies suggest synergistic benefits without increasing toxicity, though definitive long-term evidence is lacking. This review highlights how the convergence of advanced imaging, ablative technology, and systemic modulation may redefine the therapeutic paradigm of localized PCa. Further prospective, comparative trials are essential to establish the optimal combination strategies, refine patient selection, and confirm durable oncological and functional outcomes.